2021
DOI: 10.1007/s00028-021-00709-y
|View full text |Cite
|
Sign up to set email alerts
|

Regularity and time behavior of the solutions to weak monotone parabolic equations

Abstract: In this paper, we study the behavior in time of the solutions for a class of parabolic problems including the p-Laplacian equation and the heat equation. Either the case of singular or degenerate equations is considered. The initial datum $$u_0$$ u 0 is a summable function and a reaction term f is present in the problem. We prove that, despite the lack of regularity of $$u_0$$ u … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Proof of Corollary 2. The proof is similar at all to that of Corollary 1 once observed that if f ∈ L r (0, T; L σ (Ω)), with r and σ satisfying (30), by Theorem 1.3 in [8], it follows that the unique solution u 0 constructed by approximation of (11) satisfies ∇u 0 ∈ (L p (Ω T )) N .…”
Section: Proofs Of the Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Proof of Corollary 2. The proof is similar at all to that of Corollary 1 once observed that if f ∈ L r (0, T; L σ (Ω)), with r and σ satisfying (30), by Theorem 1.3 in [8], it follows that the unique solution u 0 constructed by approximation of (11) satisfies ∇u 0 ∈ (L p (Ω T )) N .…”
Section: Proofs Of the Resultsmentioning
confidence: 57%
“…We recall that if (2)-( 4) and ( 15) are satisfied for every T > 0, then there exists one and only one global solution constructed by approximation of (1) (see [30]). Theorem 1.…”
Section: Definitionmentioning
confidence: 99%